The Influence Of Multidimensional Sensory Experience On Purchase Decisions In Physical Retail In The Face Of E-Commerce Dominance - Nur Amalyna Yusrin (Jurnal Ilmiah Multidisiplin, 2025)
This study investigates the impact of five sensory dimensions, purchase intention, tactile, visual, gustative, and Olfactory, on consumer purchase decisions in physical retail environments amid the growing dominance of e-commerce. Employing a quantitative approach and Partial Least Squares Structural Equation Modelling (PLS-SEM) with data collected from 125 Mixue consumers in Jakarta area, the results indicate that only the visual and Olfactory dimensions significantly influence purchase intention. Visual stimuli emerge as the most dominant factor through the enhancement of aesthetic perceptions, while Olfactory stimuli foster positive emotional associations that encourage purchasing behaviour. Conversely, purchase intention, tactile, and gustative dimensions do not exhibit significant effects. These findings underscore the critical role of optimizing visual and Olfactory elements within multisensory marketing strategies to strengthen the attractiveness and competitiveness of physical retail stores in the digital age.